The evolution of palate shape in the Lepilemur‐Cheirogaleidae clade (Primates: Strepsirrhini). Issue 2 (14th July 2020) - Andrews, Curswan; Masters, Judith C.; Génin, Fabien; Couette, Sébastien
Abstract: Objectives: Phylogenies consistently group the folivorous Lepilemur species with the small‐bodied insectivorous‐frugivorous cheirogaleids. Juvenile lepilemurs and adult cheirogaleids share allometries in most aspects of skull morphology, except the palate. We investigated potential influences on palate shape in these taxa and several outgroups using geometric morphometrics. Materials and Methods: Our sample included representatives of four extant strepsirrhine families, Cheirogaleidae (including Lepilemurinae), Lemuridae, Indriidae, and Galagidae, and one subfossil Megaladapis . Our dataset comprised 32 landmarks collected from 397 specimens representing 15 genera and 28 species, and was analyzed using generalized procrustes analyses and between group principal component analysis. We explored the influence of size, phylogeny, diet, and the propagation of loud vocalizations on palate shape. Results: While congeneric species clustered within the morphospace, the phylomorphospace did not mirror molecular phylogenetic hypotheses of higher‐order relationships. Four palate forms were distinguished within the Cheirogaleidae. Diet, strongly linked to body size, had the single greatest influence on palate shape. The production of long‐distance advertisement calls was most often associated with positive scores on the PC1 axis. Discussion: Our results suggest that the extensive variation in palate shape among Cheirogaleidae is related to dietary shifts that accompanied changes in body size during the clade's radiation. Molecular phylogenies indicate that cheirogaleid diversification involved repeated dwarfing events, which in turn drove dietary shifts from ancestral folivory‐frugivory to frugivory, gummivory, and faunivory in the descendant species. The elongated Lepilemur palate is probably related to accelerated eruption of the cheek teeth to render juveniles competent to shear leaves upon weaning.